PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KEPUASAN PENGGUNA (DINAS KEARSIPAN DAN PERPUSTAKAAN KAB. PUNCAK JAYA) - s. tiranda, yeviana; nu graha, andi; rusno (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
Abstract This research aims to determine the effect of service quality and employee performance on user satisfaction. This research uses quantitative methods, using probability sampling techniques, namely 108 users of the Dinas Kearsipan dan Perpustakaan Kab. Puncak Jaya. The data analysis used is multiple linear regression. The research results show that competence and work discipline can increase user satisfaction, competence can increase user satisfaction, work discipline can increase user satisfaction. Suggestions to increase user satisfaction need to pay attention to emotions by prioritizing polite service, to increase competence you need to pay attention to skills by having a professional attitude and work discipline you need to pay attention to compliance with office regulations by using attributes in accordance with company regulations.